Implementation of methods of formation of readiness of future managers to use information technology in professional activities (Pedagogy of Higher and Secondary Education, 2014)
Pshenichna O. S. Implementation of methods of formation of readiness of future managers to use information technology in professional activities.Description of through methods of formation of readiness of future managers to use information technology in professional activities is considered in the article. Based on a qualitative analysis of the process of preparation of students it is identified the impact of each approach and method on preparedness components of future managers, what is presented graphically - using the matrix of influence.
Keywords: methods; method; methodical approach; information technology; readiness; readiness components; the matrix of influence